PENGELOLAAN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN FOOD AND BEVERAGE - Arifin, Mohammad Aryo (Universitas Muhammadiyah Palembang, 2018)
This research is meant to examine the influence of cash turnover, account receivable turnover, and inventoryturnover to the profitability in thefood and beverage companies which are listed in Indonesia Stock Exchange(IDX) in 2012 ? 2016 periods. The samples are 13 companies which have been selected by using purposivesampling. The financial statement data has been obtained from theIndonesia Stock Exchange (IDX). Theresearch method has been done by using descriftive verifikative method and multiplelinier regressions with theaplication instrument of SPSS (Statistical Product and Service Solutions). The result of this research shows thatcash turnover and receivable turnover have any influence to the profitability whereas the account inventoryturnover has not an influence to the profitability. The value of adjusted R square is 0.485 which shows that all ofindependent variables which are cash turnover, account receivable turnover and inventory turnover can explainthe dependent variable profitability is 48.5% and the remaining is 51.5% which is influenced by otherfactors whichare not included in this model.